Heat-conducting wave-absorbing composite material with three-dimensional interpenetrating network structure as well as preparation method and application of heat-conducting wave-absorbing composite material

By combining a three-dimensional interpenetrating network structure with a thermally conductive and absorbing composite material, carbon fiber, MXene/BNNS, and flame retardant, an electron-phonon dual transmission channel and a localized magnetic vortex structure are formed, which solves the problems of insufficient thermal conductivity, narrow absorption frequency band, and conflict between flame retardancy and absorption performance of traditional materials in 6G high-throughput chip packaging, and achieves efficient thermal management and electromagnetic compatibility.

CN120842641APending Publication Date: 2025-10-28TAICANG JIN YU ELECTRONICS MATERIALS
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510915355.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-03
Publication Date
2025-10-28

AI Technical Summary

Technical Problem

Traditional thermal conductive and absorbing materials have problems in 6G high-throughput chip packaging, such as insufficient thermal conductivity, narrow absorption frequency band, high interface thermal resistance, and conflicts between flame retardancy and absorption performance, making it difficult to meet the electromagnetic compatibility requirements of high frequency and high density.

Method used

The thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure forms an electron-phonon dual transmission channel and a local magnetic vortex structure through the synergistic effect of hydrogen bonds and chemical bonds between carbon fibers and MXene/BNNS, combined with magnetic particles and flame retardants, thereby enhancing electromagnetic wave loss. Defect-free molding with high filler content is achieved through gradient temperature curing and vacuum-assisted infusion processes.

Benefits of technology

It achieves a thermal conductivity of ≥15W/m·K, a return loss of ≥30dB@8-40GHz, and a flame retardancy rating of UL94 V-0, meeting the thermal management and electromagnetic compatibility requirements of 6G high-throughput chip packaging and solving the performance bottleneck of traditional materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005481408790000191
    Figure BDA0005481408790000191
  • Figure BDA0005481408790000201
    Figure BDA0005481408790000201
  • Figure BDA0005481408790000211
    Figure BDA0005481408790000211
Patent Text Reader

Abstract

The invention provides a heat-conducting wave-absorbing composite material with a three-dimensional interpenetrating network structure as well as a preparation method and application of the heat-conducting wave-absorbing composite material. The preparation method of the composite material comprises the following steps: impregnating carbon fibers in an ethanol dispersion liquid containing titanate, graphene quantum dots and polydopamine, carrying out low-temperature in-situ polymerization, and carrying out suction filtration and drying to obtain surface-functionalized carbon fibers; mixing the functionalized carbon fibers with an MXene / BNNS dispersion liquid, and performing freeze drying to obtain a functionalized carbon fiber three-dimensional honeycomb network skeleton; and impregnating the functionalized carbon fiber three-dimensional honeycomb network skeleton in a resin precursor solution containing a functional filler and a flame retardant to fill network gaps with resin, and heating and curing to obtain the composite material. The composite material completely meets the thermal management and electromagnetic compatibility requirements of 6G high-flux chip packaging; especially in a 6G AiP module, the material can effectively solve the problems of heat and electromagnetic interference generated by a high-power chip, and provides important support for commercial application of a 6G communication technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of 6G high-throughput chip packaging material technology, specifically relating to a thermally conductive and microwave-absorbing composite material, its preparation method and application, and particularly to a three-dimensional interpenetrating network structure thermally conductive and microwave-absorbing composite material, its preparation method and application. Background Art

[0002] As 6G communication technology evolves towards higher frequencies and higher densities, the number of electronic components integrated into high-throughput chip systems is increasing exponentially within a unit volume, and their power density has exceeded the limits of traditional electronic devices. In typical operating scenarios, the heat flux density of a single chip module can reach over 100 W / cm², leading to a sharp increase in the internal temperature gradient of the device. This extreme thermal environment not only causes reliability issues such as device performance degradation and signal transmission distortion, but also poses a risk of thermal runaway due to the accumulation of localized hot spots. Simultaneously, the rapid attenuation characteristics of electromagnetic fields in millimeter-wave bands (such as 24 GHz-100 GHz) and the dense layout of high-density electromagnetic components make it difficult for traditional electromagnetic shielding solutions to effectively suppress near-field radiation interference, posing a severe challenge to data transmission security and the device's anti-interference capabilities.

[0003] Traditional thermally conductive and microwave absorbing materials have the following limitations: (1) Insufficient thermal conductivity: The thermal conductivity of existing carbon fiber three-dimensional network thermally conductive materials is only 3W / m·K, which is difficult to meet the high heat dissipation requirements of 6G chip packaging. (2) Narrow absorption frequency band: Traditional composite fillers (such as Al2O3) + (3) High interfacial thermal resistance: Poor bonding between the filler and the resin matrix results in high interfacial thermal resistance and low thermal conductivity. (4) Conflict between flame retardant and microwave absorption performance: Existing flame retardants may release gases during combustion, which may damage the microwave absorption structure and lead to a decrease in performance.

[0004] Therefore, there is an urgent need to develop a thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure. Through collaborative innovation of materials, structure, and process, we can break through the performance bottleneck of traditional composite fillers and achieve high thermal conductivity (≥15W / m·K), wideband microwave absorption (≥30dB@8-40GHz), high strength (≥0.1MPa), and flame retardancy rating reaching UL94 V-0, thus meeting the thermal management and electromagnetic compatibility requirements of 6G high-throughput chip packaging. Summary of the Invention

[0005] Based on the deficiencies of existing technologies, the first objective of this invention is to provide a method for preparing a thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure; the second objective of this invention is to provide a thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure prepared by this method; and the third objective of this invention is to provide the application of this thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure in the preparation of thermal management and electromagnetic compatibility materials for 6G high-throughput chip systems.

[0006] The objective of this invention is achieved through the following technical solution:

[0007] On one hand, the present invention provides a method for preparing a three-dimensional interpenetrating network structure thermally conductive and microwave-absorbing composite material, comprising the following steps:

[0008] Step 1: The carbon fiber is impregnated in an ethanol dispersion containing titanate, graphene quantum dots and polydopamine, polymerized in situ at low temperature, filtered and dried to obtain surface-functionalized carbon fiber.

[0009] Step 2: The functionalized carbon fiber is mixed with MXene / BNNS dispersion and freeze-dried to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fiber.

[0010] Step 3: The functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in a resin precursor liquid containing functional fillers and flame retardants to fill the gaps in the network with resin. After heating and curing, the composite material is obtained.

[0011] In this invention, a three-dimensional interpenetrating network is formed by the synergistic interaction of surface-modified carbon fibers, two-dimensional transition metal carbides (MXene), and boron nitride nanosheets (BNNS) through hydrogen and chemical bonds. The gaps between these three-dimensional networks are filled with thermoplastic or thermosetting resins, which then chemically cross-link with the functionalized carbon fiber network to form a composite structure with excellent interfacial compatibility. The composite material of this invention meets the following performance indicators: tensile strength ≥ 0.1 MPa; thermal conductivity ≥ 15 W / m·K (XYZ triaxial anisotropy ratio ≤ 1.5); electromagnetic wave return loss ≥ 30 dB (frequency range 8-40 GHz); flame retardancy rating reaches UL94V-0; smoke density rating ≤ 15.

[0012] In the above preparation method, preferably, in step one, the ethanol dispersion containing titanate, graphene quantum dots and polydopamine has the following mass fractions: titanate is 1% to 5%; graphene quantum dots are 0.5% to 2%; and polydopamine is 3% to 8%.

[0013] In the above preparation method, preferably, the carbon fiber has a diameter of 5-25 μm and a length of 50-500 μm.

[0014] In the above preparation method, preferably, the temperature of the low-temperature in-situ polymerization is 20℃~50℃ and the time is 4~8h.

[0015] In the above preparation method, preferably, in step two, the weight ratio of the functionalized carbon fiber to the MXene / BNNS dispersion is 1:3.

[0016] In the above preparation method, preferably, the preparation of the MXene / BNNS dispersion includes: mixing and dispersing MXene sheets and boron nitride nanosheets in an N-methylpyrrolidone solution.

[0017] In the above preparation method, preferably, the mass ratio of the MXene sheet to the boron nitride nanosheet is 1:2 to 1:4.

[0018] In the above preparation method, preferably, the thickness of the MXene sheet is 1-5 nm and the lateral dimension is 1-10 μm.

[0019] In the above preparation method, preferably, the thickness of the boron nitride nanosheets is 10-50 nm and the lateral dimension is 0.5-5 μm.

[0020] In the above preparation method, preferably, the freeze-drying method is the ice template method, the freezing temperature is -20 to -15℃, the dynamic cooling rate is 1℃ / min, and the drying time is 20 to 24h.

[0021] In this invention, freeze-drying is performed with the aid of an ice template to form a three-dimensional honeycomb network framework by utilizing the hydrogen bonding between the -OH groups on the MXene surface and the -NH2 groups on the BNNS edge. In this three-dimensional network structure, MXene sheets and BNNS sheets are stacked alternately in a "brick-and-mortar" structure and are bridged by TiO2 nanoparticles on the carbon fiber surface to form an electron-phonon dual transport channel. Magnetic particles form a localized magnetic vortex structure in the resin matrix through magnetic coupling, enhancing electromagnetic wave loss. The interlayer spacing of the MXene / BNNS hydrogen bond network is 1.4–1.5 nm, significantly higher than the 1.23 nm of pure MXene.

[0022] In the above preparation method, preferably, the solid content of the MXene / BNNS dispersion is 5% to 15%.

[0023] In the above preparation method, preferably, in step three, the preparation method of the resin precursor liquid containing functional fillers and flame retardants includes:

[0024] Core-shell magnetic particles and high thermal conductivity ceramics are mixed, then modified with silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0025] In the above preparation method, preferably, the weight ratio of the core-shell structured magnetic particles, the high thermal conductivity ceramic, the flame retardant nanocapsules and the resin matrix is ​​2:1:1:1.

[0026] In the above preparation method, preferably, the core-shell structured magnetic particles are prepared by coating the surface of the iron oxide nanoparticle core with a silicon dioxide shell through a sol-gel method; wherein, the core particle size is 50-200 nm; the shell is SiO2 with a thickness of 10-30 nm.

[0027] In the above preparation method, preferably, the high thermal conductivity ceramic is selected from aluminum nitride and / or boron nitride, but is not limited thereto.

[0028] In the above preparation method, preferably, the method for preparing the flame retardant nanocapsules includes:

[0029] Ammonium polyphosphate and melamine cyanurate are mixed and used as a flame retardant core material;

[0030] A polyurethane / haloysite composite capsule wall is formed on the surface of the core material by in-situ polymerization.

[0031] In the above preparation method, preferably, the mass ratio of the ammonium polyphosphate and the melamine cyanurate is 3:7.

[0032] In the above preparation method, preferably, the particle size of the flame retardant nanocapsules is 100-500 nm.

[0033] In the above preparation method, preferably, the resin matrix is ​​a blend system of polyimide and polybenzoxazole, and the blending mass ratio of polyimide and polybenzoxazole is 5:3 to 7:3.

[0034] In this invention, polyimide provides high-temperature resistance, and polybenzoxazole forms π-π conjugation with the surface functional groups of the functional filler through the benzoxazole ring in the molecular chain, thereby reducing the interfacial thermal resistance.

[0035] In the above preparation method, preferably, in step three, the functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in a resin precursor liquid containing functional fillers and flame retardants so that the resin fills the gaps in the network. The process is vacuum-assisted infusion with a pressure of 0.3 to 0.5 MPa.

[0036] In the above preparation method, preferably, gradient temperature curing is adopted, specifically: first, curing at 80℃ for 10-30 min; then curing at 150℃ for 30-60 min; and finally curing at 220℃ for 10-30 min.

[0037] On the other hand, the present invention also provides a thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure, which is prepared by the above-described preparation method.

[0038] Furthermore, the present invention also provides the application of the above-mentioned composite material in the preparation of thermal management and electromagnetic compatibility materials for 6G high-throughput chip systems.

[0039] The beneficial effects of this invention are:

[0040] The thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure of the present invention has the following advantages compared with the prior art:

[0041] (1) Improved thermal conductivity. Through the three-dimensional interpenetrating network structure and interfacial chemical bonding, the thermal conductivity can reach 15-40 W / m·K, which is much higher than that of traditional carbon fiber three-dimensional network (3 W / m·K) and MXene / epoxy resin composite material (7.31 W / m·K).

[0042] (2) Wideband absorption capability. The combination of Fe3O4@SiO2 core-shell structure and three-dimensional network can achieve a return loss of ≥30dB in the 8-40GHz frequency band, which is significantly better than traditional composite materials (such as CoNi@BN / PDMS composite material, which only reaches -49.9dB in the 3.92-6.32GHz frequency band).

[0043] (3) Reduced interfacial thermal resistance. The TiO2 transition layer on the carbon fiber surface reduces the interfacial thermal resistance by more than 40% through Ti-OC bonds, and the interlayer spacing of the MXene / BNNS hydrogen bond network is expanded to 1.4-1.5 nm, which promotes phonon transport.

[0044] (4) Synergistic effect of flame retardancy and electromagnetic wave absorption. The phosphorus-nitrogen flame retardant nanocapsules release PO free radicals, which synergistically form a dense carbon layer with MXene sheets, while enhancing electromagnetic wave loss through interfacial polarization; the NH3 produced by the decomposition of the flame retardant reacts with BNNS to generate BNO. x A wide-bandgap insulation layer suppresses leakage current and achieves a synergistic improvement in flame retardancy and wave absorption performance.

[0045] (5) It can be prepared on a large scale. Low-temperature in-situ polymerization (-20℃) combined with ice template directional freeze drying avoids the problems of MXene oxidation and BNNS stacking caused by high-temperature treatment; the vacuum-assisted infusion process controls the resin flow through pressure gradient, achieving defect-free molding with a high filler content of more than 90%.

[0046] The thermally conductive and electromagnetically absorbing composite material with a three-dimensional interpenetrating network structure developed in this invention has a thermal conductivity ≥15W / m·K, a return loss ≥30dB@8-40GHz, and a flame retardant rating of UL94 V-0, fully meeting the thermal management and electromagnetic compatibility requirements of 6G high-throughput chip packaging. Especially in 6G AiP (Antenna-in-Package) modules, this material can effectively solve the heat and electromagnetic interference problems generated by high-power chips, providing important support for the commercial application of 6G communication technology.

[0047] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention will be described in detail below. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. The processes, conditions, reagents, experimental methods, etc., for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and general knowledge in the art, and the present invention does not have any special limitations.

[0049] Example 1:

[0050] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0051] (1) Surface functionalization of carbon fiber:

[0052] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0053] (2) Preparation of MXene / BNNS dispersion:

[0054] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0055] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0056] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0057] (4) Preparation of core-shell structured magnetic particles:

[0058] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0059] (5) Preparation of flame retardant nanocapsules:

[0060] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0061] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0062] (6) Preparation of resin matrix:

[0063] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0064] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0065] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0066] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0067] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0068] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0069] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0070] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0071] Tensile strength: 0.25 MPa

[0072] Thermal conductivity: 30 W / m·K in-plane, 22 W / m·K out-of-plane (anisotropy ratio 1.36)

[0073] Return loss: -40dB@20GHz (8~40GHz band)

[0074] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0075] Smoke density rating: 12

[0076] Example 2:

[0077] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0078] (1) Surface functionalization of carbon fiber:

[0079] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0080] (2) Preparation of MXene / BNNS dispersion:

[0081] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:3 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0082] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0083] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0084] (4) Preparation of core-shell structured magnetic particles:

[0085] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0086] (5) Preparation of flame retardant nanocapsules:

[0087] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0088] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0089] (6) Preparation of resin matrix:

[0090] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0091] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0092] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0093] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0094] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0095] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0096] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0097] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0098] Tensile strength: 0.20 MPa

[0099] Thermal conductivity: 25 W / m·K in-plane, 18 W / m·K out-of-plane (anisotropy ratio 1.39)

[0100] Return loss: -45dB@10GHz (8~13GHz band bandwidth 5GHz)

[0101] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0102] Smoke density rating: 14

[0103] Example 3:

[0104] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0105] (1) Surface functionalization of carbon fiber:

[0106] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0107] (2) Preparation of MXene / BNNS dispersion:

[0108] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:3 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0109] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0110] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0111] (4) Preparation of core-shell structured magnetic particles:

[0112] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0113] (5) Preparation of flame retardant nanocapsules:

[0114] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0115] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0116] (6) Preparation of resin matrix:

[0117] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 5:5.

[0118] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0119] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0120] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0121] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0122] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0123] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0124] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0125] Tensile strength: 0.35 MPa

[0126] Thermal conductivity: 22 W / m·K in-plane, 19 W / m·K out-of-plane (anisotropy ratio 1.16)

[0127] Return loss: -38dB@25GHz (8-40GHz band)

[0128] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0129] Smoke density rating: 11

[0130] Example 4:

[0131] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0132] (1) Surface functionalization of carbon fiber:

[0133] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0134] (2) Preparation of MXene / BNNS dispersion:

[0135] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 15%.

[0136] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0137] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0138] (4) Preparation of core-shell structured magnetic particles:

[0139] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0140] (5) Preparation of flame retardant nanocapsules:

[0141] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0142] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0143] (6) Preparation of resin matrix:

[0144] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0145] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0146] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0147] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0148] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0149] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0150] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0151] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0152] Tensile strength: 0.18 MPa

[0153] Thermal conductivity: 35 W / m·K in-plane, 26 W / m·K out-of-plane (anisotropy ratio 1.35)

[0154] Return loss: -32dB@18GHz (8-11GHz band bandwidth 3GHz)

[0155] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0156] Smoke density rating: 15

[0157] Example 5:

[0158] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0159] (1) Surface functionalization of carbon fiber:

[0160] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (5% by mass), graphene quantum dots (1% by mass), and polydopamine (10% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 100 nm.

[0161] (2) Preparation of MXene / BNNS dispersion:

[0162] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0163] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0164] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0165] (4) Preparation of core-shell structured magnetic particles:

[0166] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0167] (5) Preparation of flame retardant nanocapsules:

[0168] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0169] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0170] (6) Preparation of resin matrix:

[0171] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0172] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0173] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0174] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0175] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0176] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0177] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0178] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0179] Tensile strength: 0.15 MPa

[0180] Thermal conductivity: 38 W / m·K in-plane, 28 W / m·K out-of-plane (anisotropy ratio 1.36)

[0181] Return loss: -35dB@35GHz (8-40GHz band)

[0182] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0183] Smoke density rating: 13

[0184] Example 6:

[0185] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0186] (1) Surface functionalization of carbon fiber:

[0187] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0188] (2) Preparation of MXene / BNNS dispersion:

[0189] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0190] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0191] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0192] (4) Preparation of core-shell structured magnetic particles:

[0193] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0194] (5) Preparation of resin matrix:

[0195] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0196] (6) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0197] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into a matrix containing ammonium polyphosphate and resin to form a uniformly dispersed filler cluster, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0198] The mass ratio of the core-shell structured magnetic particles to the ammonium polyphosphate and the resin matrix is ​​2:1:1.

[0199] (7) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0200] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0201] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0202] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0203] Tensile strength: 0.22 MPa

[0204] Thermal conductivity: 28 W / m·K in-plane, 20 W / m·K out-of-plane (anisotropy ratio 1.40)

[0205] Return loss: -28dB@25GHz (8-35GHz band)

[0206] Flame retardant rating: UL94 V-2 (self-extinguishing time 15 seconds, molten droplets ignite cotton pad)

[0207] Smoke density rating: 21

[0208] Example 7:

[0209] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0210] (1) Surface functionalization of carbon fiber:

[0211] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0212] (2) Preparation of MXene / BNNS dispersion:

[0213] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0214] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0215] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0216] (4) Preparation of core-shell structured magnetic particles:

[0217] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0218] (5) Preparation of flame retardant nanocapsules:

[0219] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0220] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0221] (6) Preparation of resin matrix:

[0222] A resin matrix was prepared by blending polyimide and polybenzoxazole at a mass ratio of 7:3.

[0223] (7) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0224] Core-shell magnetic particles and high thermal conductivity ceramic (boron nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0225] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the resin matrix is ​​2:1:1.

[0226] (8) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0227] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0228] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0229] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0230] Tensile strength: 0.28 MPa

[0231] Thermal conductivity: 32 W / m·K in-plane, 25 W / m·K out-of-plane (anisotropy ratio 1.28)

[0232] Return loss: -42dB@15GHz (8-20GHz band bandwidth 12GHz)

[0233] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0234] Smoke density rating: 10

[0235] Example 8:

[0236] This embodiment provides a three-dimensional interpenetrating network structure thermally conductive and microwave absorbing composite material and its preparation method. The preparation method of the composite material includes:

[0237] (1) Surface functionalization of carbon fiber:

[0238] Carbon fibers with a diameter of 10 μm and a length of 100 μm were impregnated in an ethanol dispersion containing titanate (3% by mass), graphene quantum dots (1% by mass), and polydopamine (5% by mass). The mixture was then subjected to low-temperature in-situ polymerization and stirring at 30 °C for 6 h. After the reaction was completed, the mixture was filtered and dried to obtain surface-functionalized carbon fibers. The polydopamine coating thickness of the surface-functionalized carbon fibers was 50 nm.

[0239] (2) Preparation of MXene / BNNS dispersion:

[0240] The slurry was prepared by mixing and dispersing MXene sheets and boron nitride nanosheets at a mass ratio of 1:4 in an N-methylpyrrolidone solution, with a solid content of 10%.

[0241] (3) Fabrication of functionalized carbon fiber three-dimensional honeycomb network skeleton:

[0242] Functionalized carbon fibers were mixed with MXene / BNNS dispersion at a weight ratio of 1:3, and then freeze-dried at -20℃ for 24h with a dynamic cooling rate of 1℃ / min to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fibers.

[0243] (4) Preparation of core-shell structured magnetic particles:

[0244] A core-shell structured magnetic particle was prepared by coating the surface of the core of iron oxide nanoparticles with a silica shell using a conventional sol-gel method. The core particle size was 50–200 nm, and the shell was SiO2 with a thickness of 10–30 nm.

[0245] (5) Preparation of flame retardant nanocapsules:

[0246] Ammonium polyphosphate and melamine cyanurate were mixed at a mass ratio of 3:7 to serve as a flame retardant core material.

[0247] Flame retardant nanocapsules were obtained by forming a polyurethane / haloysite composite capsule wall on the surface of the core material using a conventional in-situ polymerization method.

[0248] (6) Preparation of resin precursor liquid containing functional fillers and flame retardants:

[0249] Core-shell magnetic particles and high thermal conductivity ceramic (aluminum nitride) are mixed at a mass ratio of 2:1, then modified with conventional silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and polyurethane to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants.

[0250] The mass ratio of the core-shell magnetic particles to the flame retardant nanocapsules and the polyurethane is 2:1:1.

[0251] (7) Preparation of thermally conductive and microwave-absorbing composite materials with a three-dimensional interpenetrating network structure:

[0252] Functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in resin precursor liquid containing functional filler and flame retardant, and vacuum-assisted infusion process is used at a pressure of 0.3 MPa to fill the gaps in the network with resin.

[0253] Next, a gradient temperature curing method was used, specifically: first, curing at 80℃ for 15 min; then curing at 150℃ for 30 min; and finally curing at 220℃ for 15 min; the composite material was obtained after curing.

[0254] The composite material prepared in this embodiment was subjected to performance tests including tensile strength, thermal conductivity, return loss, flame retardancy rating, and smoke density rating. The test results are as follows:

[0255] Tensile strength: 0.40 MPa

[0256] Thermal conductivity: 20 W / m·K in-plane, 16 W / m·K out-of-plane (anisotropy ratio 1.25)

[0257] Return loss: -33dB@18GHz (8-30GHz band)

[0258] Flame retardant rating: UL94 V-0 (self-extinguishing time <10 seconds, no dripping)

[0259] Smoke density rating: 15

[0260] Experimental Data Analysis and Conclusions

[0261] (1) Thermal conductivity analysis: The thermal conductivity of Examples 1 to 8 was tested using the ASTM D5470 standard test method (temperature gradient 50℃, pressure 3000kPa), and the results are shown in Table 1 below.

[0262] Table 1:

[0263]

[0264] The experimental data analysis in Table 1 shows that the three-dimensional interpenetrating network structure is the key factor for improving thermal conductivity. The thermal conductivity of Examples 1 to 5 is higher than that of the traditional three-dimensional carbon fiber network (3 W / m·K) and MXene / epoxy resin composite material (7.31 W / m·K).

[0265] The thermal conductivity is optimal when the MXene / BNNS mass ratio is 1:4; when the ratio is adjusted to 1:3, the thermal conductivity decreases slightly, but the microwave absorption performance improves.

[0266] When the solid content of the ice template method is 10%, the thermal conductivity and microwave absorption performance reach the best balance; when the solid content is increased to 15%, the thermal conductivity is further improved, but the microwave absorption bandwidth is narrowed.

[0267] Surface functionalization of carbon fiber (3% titanate content) can effectively reduce interfacial thermal resistance and improve thermal conductivity.

[0268] (2) Absorption performance analysis: The return loss of Examples 1 to 8 was tested by a vector network analyzer (VNA) (frequency range 8 to 40 GHz), and the results are shown in Table 2 below.

[0269] Table 2:

[0270]

[0271] Analysis of the experimental data in Table 2 shows that the Fe3O4@SiO2 core-shell structure is the core factor for improving the microwave absorption performance. The return loss of Examples 1 to 5 is higher than that of traditional composite materials (such as the CoNi@BN / PDMS composite material, which only reaches -49.9dB in the 3.92 to 6.32 GHz frequency band).

[0272] When the MXene / BNNS mass ratio is 1:4, the microwave absorption performance and thermal conductivity are optimally balanced; when the ratio is adjusted to 1:3, the microwave absorption bandwidth is further expanded, but the thermal conductivity decreases slightly.

[0273] The three-dimensional interpenetrating network structure provides multiple scattering and reflection paths for electromagnetic waves, effectively broadening the absorption frequency band. Examples 1 to 5 can all cover the 8 to 40 GHz frequency band.

[0274] The synergistic effect of phosphorus-nitrogen flame retardant nanocapsules and MXene can further improve the microwave absorption performance. The return loss of Example 1 is 7 dB higher than that of Example 6.

[0275] (3) Flame retardant performance analysis: The flame retardant performance of Examples 1 to 8 was evaluated by UL94 vertical burning test and cone calorimeter (ISO 5660-1) test. The results are shown in Table 3 below.

[0276] Table 3:

[0277]

[0278] Analysis of the experimental data in Table 3 shows that phosphorus-nitrogen flame retardant nanocapsules are the key factor in improving flame retardant performance. Examples 1 to 5 all achieved the UL94 V-0 rating, while Example 6, after being replaced with a single component of ammonium polyphosphate, only achieved the V-2 rating.

[0279] When the nanocapsule size is 100-500nm, the flame retardant releases PO free radicals, which synergistically form a dense carbon layer with the MXene sheets, effectively isolating oxygen and inhibiting combustion.

[0280] The NH3 produced by the decomposition of flame retardant reacts with BNNS to produce BNO. x A wide-bandgap insulation layer suppresses leakage current and achieves a synergistic improvement in flame retardancy and wave absorption performance.

[0281] (4) Mechanical property analysis: The mechanical properties of Examples 1-8 were evaluated by tensile strength test (GB / T 1040.2-2006 standard), and the results are shown in Table 4 below.

[0282] Table 4:

[0283]

[0284] Analysis of the experimental data in Table 4 shows that the resin matrix ratio and the content of functional fillers directly affect the mechanical properties of the composite material. Example 3 (5:5 ratio) and Example 8 (polyurethane matrix) have the best mechanical properties.

[0285] The surface functionalization treatment of carbon fiber (polydopamine coating thickness of 50nm) can effectively improve the interfacial bonding strength of composite materials. The tensile strength of Examples 1 to 4 is higher than that of Example 5 (100nm coating).

[0286] The three-dimensional interpenetrating network structure provides good support for the composite material, and the tensile strength of Examples 1 to 8 all meet the technical requirement of ≥0.1MPa.

[0287] Comparative experiments to verify:

[0288] (1) Compared with traditional carbon fiber three-dimensional network: The thermal conductivity of the present invention is 30W / m·K (in-plane), while that of traditional carbon fiber three-dimensional network is only 3W / m·K.

[0289] (2) Compared with MXene / epoxy resin composite material: The thermal conductivity of the present invention is 30 W / m·K, while that of MXene / epoxy resin composite material is only 7.31 W / m·K.

[0290] (3) Compared with CoNi@BN / PDMS composite material: The absorption frequency band of the present invention covers 8 to 40 GHz, while the CoNi@BN / PDMS composite material only reaches -49.9 dB in the 3.92-6.32 GHz band.

[0291] (4) Compared with the MPP / PAPP compound flame retardant system: The flame retardant content of the present invention is only 5%, while the MPP / PAPP compound flame retardant system requires 30% flame retardant content to achieve the UL94 V-0 rating.

[0292] In summary, this invention, through synergistic innovation in materials, structure, and process, successfully developed a three-dimensional interpenetrating network structure for thermally conductive and microwave-absorbing composite materials. The main innovations include:

[0293] (1) Multifunctional integrated filler design: By assembling MXene (high conductivity) and BNNS (high thermal conductivity) through hydrogen bonding, combined with the electromagnetic loss characteristics of Fe3O4@SiO2 magnetic particles, the thermal conductivity and microwave absorption performance of a single filler system can be controlled simultaneously.

[0294] (2) Innovation of three-dimensional interpenetrating network structure: The ice template method is used to construct a three-dimensional honeycomb network of MXene / BNNS / carbon fiber. Its pore size (5~50μm) is matched with the resin injection dynamics to ensure defect-free filling; the XYZ three-dimensional continuous thermal conduction path design breaks through the anisotropy limitation of traditional compound fillers.

[0295] (3) Interface synergistic optimization technology: The TiO2 transition layer on the carbon fiber surface is connected to the resin matrix through Ti-OC bonds, reducing the interfacial thermal resistance by more than 40%; the polydopamine-modified MXene forms a dynamic hydrogen bond network with the edge amino groups of BNNS, improving the impact resistance of the composite material.

[0296] (4) Synergistic effect of flame retardancy and electromagnetic wave absorption: When phosphorus-nitrogen flame retardant nanocapsules are burned, they release PO free radicals, which synergistically form a dense carbon layer with MXene sheets, while enhancing electromagnetic wave loss through interfacial polarization; NH3 produced by the decomposition of flame retardant reacts with BNNS to generate BNO. x Wide gap insulation layer to suppress leakage current.

[0297] (5) Scalable preparation process: Low-temperature in-situ polymerization (-20℃) combined with ice template directional freeze drying avoids MXene oxidation and BNNS stacking problems caused by high-temperature treatment; Vacuum-assisted infusion process controls resin flow through pressure gradient to achieve defect-free molding with a high filler content of over 90%.

[0298] Specific embodiments have been used to illustrate the principles and implementation methods of this invention. The descriptions of the embodiments above are only for the purpose of helping to understand the method and core ideas of this invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this invention. Therefore, the content of this specification should not be construed as a limitation of this invention.

Claims

1. A method for preparing a three-dimensional interpenetrating network structure thermally conductive and microwave-absorbing composite material, characterized in that, The following steps are involved: Step 1: The carbon fiber is impregnated in an ethanol dispersion containing titanate, graphene quantum dots and polydopamine, polymerized in situ at low temperature, filtered and dried to obtain surface-functionalized carbon fiber. Step 2: The functionalized carbon fiber is mixed with MXene / BNNS dispersion and freeze-dried to obtain a three-dimensional honeycomb network skeleton of functionalized carbon fiber. Step 3: The functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in a resin precursor liquid containing functional fillers and flame retardants to fill the gaps in the network with resin. After heating and curing, the composite material is obtained.

2. The preparation method according to claim 1, characterized in that: In step one, in the ethanol dispersion containing titanate, graphene quantum dots, and polydopamine, the mass fraction of titanate is 1% to 5%; the mass fraction of graphene quantum dots is 0.5% to 2%; and the mass fraction of polydopamine is 3% to 8%. Preferably, the carbon fiber has a diameter of 5–25 μm and a length of 50–500 μm; Preferably, the low-temperature in-situ polymerization is carried out at a temperature of 20°C to 50°C for 4 to 8 hours.

3. The preparation method according to claim 1, characterized in that: In step two, the weight ratio of the functionalized carbon fiber to the MXene / BNNS dispersion is 1:3; Preferably, the preparation of the MXene / BNNS dispersion includes: mixing and dispersing MXene sheets and boron nitride nanosheets in an N-methylpyrrolidone solution; Preferably, the mass ratio of the MXene sheet to the boron nitride nanosheet is 1:2 to 1:4; Preferably, the thickness of the MXene sheet is 1–5 nm, and the lateral dimension is 1–10 μm; Preferably, the boron nitride nanosheets have a thickness of 10–50 nm and a lateral dimension of 0.5–5 μm; Preferably, the freeze-drying method is the ice template method, the freezing temperature is -20 to -15℃, the dynamic cooling rate is 1℃ / min, and the drying time is 20 to 24 hours; Preferably, the solid content of the MXene / BNNS dispersion is 5% to 15%.

4. The preparation method according to claim 1, characterized in that: In step three, the method for preparing the resin precursor liquid containing functional fillers and flame retardants includes: Core-shell magnetic particles and high thermal conductivity ceramics are mixed, then modified with silane coupling agents, and finally electrostatically self-assembled into flame retardant nanocapsules and resin matrix to form uniformly dispersed filler clusters, thus obtaining a resin precursor liquid containing functional fillers and flame retardants. Preferably, the weight ratio of the core-shell magnetic particles, the high thermal conductivity ceramic, the flame retardant nanocapsules, and the resin matrix is ​​2:1:1:

1.

5. The preparation method according to claim 4, characterized in that: The core-shell structured magnetic particles are formed by coating the surface of the iron oxide nanoparticle core with a silicon dioxide shell using a sol-gel method; wherein the core particle size is 50-200 nm; and the shell is SiO2 with a thickness of 10-30 nm. Preferably, the high thermal conductivity ceramic is selected from aluminum nitride and / or boron nitride.

6. The preparation method according to claim 4, characterized in that: The method for preparing the flame retardant nanocapsules includes: Ammonium polyphosphate and melamine cyanurate are mixed and used as a flame retardant core material; A polyurethane / haloite composite capsule wall is formed on the surface of the core material by in-situ polymerization. Preferably, the mass ratio of the ammonium polyphosphate to the melamine cyanurate is 3:7; Preferably, the flame retardant nanocapsules have a particle size of 100–500 nm.

7. The preparation method according to claim 4, characterized in that: The resin matrix is ​​a blend of polyimide and polybenzoxazole, and the mass ratio of the polyimide to the polybenzoxazole is 5:3 to 7:

3.

8. The preparation method according to claim 1, characterized in that: In step three, the functionalized carbon fiber three-dimensional honeycomb network skeleton is impregnated in a resin precursor liquid containing functional fillers and flame retardants to fill the gaps in the network with resin. The process is vacuum-assisted infusion at a pressure of 0.3 to 0.5 MPa. Preferably, a gradient temperature curing method is used, specifically: first, curing at 80℃ for 10-30 min; then curing at 150℃ for 30-60 min; and finally curing at 220℃ for 10-30 min.

9. A thermally conductive and microwave-absorbing composite material with a three-dimensional interpenetrating network structure, which is prepared by the preparation method described in any one of claims 1 to 8.

10. The application of the composite material of claim 9 or the composite material prepared by any one of claims 1 to 8 in the preparation of thermal management and electromagnetic compatibility materials for 6G high-throughput chip systems.

Citation Information

Cited By

  • Functional network structure design method and application of high-thermal-conductivity wave-absorbing composite material

    CN121930612A